INTENSITAS PEMBUKAAN WILAYAH HUTAN DAN EKSTRAKSI KAYU DALAM PENGUSAHAAN HUTAN ALAM DI LUARJAWA - Djaban Tinambunan (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
An investigation of forest infrastructure and wood extraclion intensilies was conducted in 10 logging componies in dry land forests and olver 10 logging companies in swamp forests outside Java from 1989 to 1991.For dry land forests, it is found that average values of road density (combined main and ranck roads) is 13 mlha, commercial wood valume available for harvesting is 56 cu.mlha, and the realizalion of wood extraclion is 41 cu.mlha. An amount of commercial volume left unutilized in the forest (wood Waste) ir 15 cu.mlha. While in swamp forats, lhose figures are consecutively 11 mlha, 43 cu.mlha, 32.cu.mlha and 11 cu.mllta. Staitstctllly, all the above valuts of dry and swamp forests are not significanly different.The above facts imply shat, nationwide, the high level of commercial wood waste does occur. Our estimale shows thet the figure could reach at least 3.7 million cu.m per year.efforts need to be done by all parties concmed to reduce shat waste to the minimum level.